Law and Religion: A Feminist Biblical-Theological Critique - Chakkalakal, Pauline (Journal of Dharma, 2007)
Jesus of Nazareth was teaching in a synagogue on a Sabbath day. There came a crippled woman, who was bent over for 18 years. When Jesus saw her, he called out to her, placed his hands on her and healed her saying, "Woman, you are set free from your ailment." Instantly she stood up straight and began praising God (Lk, 13:10-13). The law-abiding synagogue official was angry that Jesus had healed her on the Sabbath. He expressed his contention with all his religious fervour: "There are six days on which work ought to be done; come on those days and be cured, and not on the Sabbath day" (v. 14). Struck by his fanatic belief, the Master responded: "You hypocrites! Does not each of you on the Sabbath untie his ox or his donkey from the manger, and lead it away to give it water? And ought not his woman, a daughter of Abraham whom Satan bound for eighteen long years, be set free from this bondage on the Sabbath day?" (vv. 15-16).